Findings from the Munich longitudinal study of giftedness and their impact on identification, gifted education and counseling - Heller, K. A. (Talent Development & Excellence, 2013)
The Munich Longitudinal Giftedness Study (MLGS), originally carried out from 1985 to 1989 and completed by two follow-ups in the nineties, focused on three aims in the first project phase and on five aims in the second phase. From the midnineties to the end of 2010, many consecutive studies based on the theoretical and empirical results of the MLGS have been implemented at the Center for the Study of Giftedness at Ludwig Maximilians University (LMU) of Munich. First of all, the "Munich Model of Giftedness" (MMG) and the extended version "Munich Dynamic Ability Achievement Model" (MDAAM) will be explained as the theoretical frame of the MLGS and the following investigations. After methodological remarks, selected findings of the MLGS are presented in greater detail. Practical applications to identifying gifted individuals and talent search for gifted programs are in the center of the following section. Of special interest should be MMG- and MDAAM-based scientifically evaluated intervention strategies and measures for enhancing individual potentials versus measures for reducing ineffective or dysfunctional motivation variables and self-concept patterns, e.g. with regard to STEM- and at-risk-groups. Finally, some conclusions will be discussed.